Managing professional people : understanding creative performance - Shapero, Albert (New York : The free press; London : Collier Mamillan, 1985)
This book explores traditional myths about the nature of professional work and provides valuable insights into the management of professional.
Includes index.
Includes bibliographic references:p. 231-240.
ijb 30/08/2018
Loans
Keywords: Professions; Personnel management